Assessing acceptance of service staff towards employee with disabilty in hotel industry / Nurul’ Aishah@N Zakaria ...[et al.] - Zakaria, Nurul’ Aishah@N; Mat Noor, Syuhirdy; Mohamed Rani, Zaharah; Mohd Akhir, Irina; Rozekhi, Nor Azureen; Abd Hakim, Fairuz; Md Tahir, Nurhidayah (Universiti Teknologi MARA Cawangan Pulau Pinang, 2020)
An issue of employment of disability people in a hotel industry is a prolong issue that discussing on discrimination towards the disability people in the world of employment. This study focuses on the acceptance of service staff toward employee with disability using economic model and social model (Sajid, 2009). The sample for this study was the service staff of hotel in Seberang Perai, Penang that hired disability people. The service staffs consist of male and female aged from 18 to 60 years old from four departments which are food and beverages, front office, housekeeping and kitchen. Questionnaire has been distributed to 86 respondents using Likert scale. The findings of this study identified the service staff accept the people with disability by giving more job opportunity and equal treat among employees (economic model) and able to communicate, work as a team, give cooperation and sharing information each other (social model). However, the service staffs are neither agreeing nor disagree in suggesting the different working area for the disability employee. The results can be used by the Hotel employers in understanding the acceptance of non-disable employees towards disable employees and the relationship between them for better working environment.